1986
DOI: 10.1111/j.2044-8341.1986.tb02668.x
|View full text |Cite
|
Sign up to set email alerts
|

The Type A behaviour pattern as a precursor to stressful life‐events: A confluence of coronary risks

Abstract: Both the Type A Behaviour Pattern (TABP) and the presence of stressful life-events have been independently established as precursors to the onset of coronary heart disease (CHD). The thematic character of the TABP suggests, however, that the two phenomena might be linked, to the extent that features of the TABP may place an individual in social, occupational and personal circumstances which enhance the probability of encountering stressful life-events. Evidence from survivors of clinical CHD gives some support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

1988
1988
1996
1996

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 14 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…They strive to obtain the most from the environment in the shortest possible time (Matthews and Haynes, 1986). Their lifestyle exposes them to a wide range of self-initiated stressful life-events (Byrne and Rosenman, 1986). They set extremely high performance goals (Matthews, 1982) and work on multiple projects at once (Lee, Earley and Hanson, 1988).…”
Section: Type a Behavior Patternmentioning
confidence: 99%
“…They strive to obtain the most from the environment in the shortest possible time (Matthews and Haynes, 1986). Their lifestyle exposes them to a wide range of self-initiated stressful life-events (Byrne and Rosenman, 1986). They set extremely high performance goals (Matthews, 1982) and work on multiple projects at once (Lee, Earley and Hanson, 1988).…”
Section: Type a Behavior Patternmentioning
confidence: 99%
“…The underlying basis for this type A competitiveness may be a deepseated, covert anxiety that is associated with insecurity and fear of failure, and different from neuroticism in the latter's usual construct. [27][28][29][30][31] Relationship to CHD TABP was related to CHD prevalence in several studies,16 and then found prospectively associated with significantly higher incidence of initial CHD during an 8.5-year follow-up in the Western Collaborative Group Study (WCGS).' This relationshi but not in some later ~tudies.…”
Section: Behavior Patternsmentioning
confidence: 99%
“…A social psychological perspective would also be valuable as social situa-tions can elicit o r exacerbate subjective and physiological stress reactions in Type A individuals, and thus compromise health (Bruch, McCann, & Harvey, 1991;Byrne & Rosenman, 1986;Smith, 1992;Smith & Anderson, 1986). Research on, for example, the situations Type A individuals choose to enter (Margolis, McLeroy, Runyan, & Kaplan, 1983;Smith & Anderson, 1986), the types of emotions they are likely to experience (Suls & Wan, 1989), and the nature of their marital relations (Sanders, Smith, & Alexander, 1991;Sullaway & Morell, 1990) can shed light on how naturalistic situations influence health.…”
mentioning
confidence: 99%